Comparison of Skin Staples versus Skin Sutures After Inguinal Hernioplasty in Terms of Surgical Site Infection - Muhammad Ali; Muhammad Ghayasuddin; Syeda Mahnoor Ali Shah; Ramsha Waseem; Wahb; Khadijah Abid (ziauddin University, 2024)
Background: Surgical site infection is a major concern following inguinal hernia repair, potentially leading to extended hospital stays, increased morbidity, patient discomfort, and higher healthcare costs. This study aimed to conduct a comparative analysis between skin staples and skin sutures in inguinal hernioplasty, explicitly focusing on their impact on surgical site infection rates. Methods: From September 2022 to June 2023, a randomized control trial study was carried out at the Surgery Department, Kulsoom Bai Valika Hospital Karachi. A total of 100 patients who underwent Lichtenstein tension-free mesh hernioplasty were allocated into two groups: the stapler group (n=50) and the polypropylene suture group (n=50). The patients were monitored for 3 to 6 hours post-surgery and safely discharged on the first postoperative day. Follow-up was scheduled 7 days after surgery to assess wound complications, specifically surgical site infections. Comparison between both groups was done using the Chi-square/Fisher exact test for surgical site infection and independent samples t-test for pain score. The level of significance was set at 5%. Results: The incidence of postoperative pain was slightly lower in the stapler group compared to the suture group (10% vs. 16%), this difference was not statistically significant (p=0.544). Moreover, the surgical site infection rate was significantly lower in the stapler group (3%) than in the suture group (12%) with p=0.012. Conclusion: When securing the mesh in inguinal hernia cases, the utilization of skin staples was considered a safe approach and was associated with lower surgical site infection as compared to skin sutures.